Evaluation of the Ponticulus Posticus with Cone-Beam Computed Tomography in a Turkish Population - Erdem, Suheda; Gunduz, Kaan; Kasap, Pelin (Wolters Kluwer Medknow Publications, 2023)
Introduction: The aim of this study was to investigate the incidence of ponticulus posticus (PP) in a sample population with cone-beam computed tomography (CBCT). Materials and Methods: The images of 1000 patients who were examined CBCT were analyzed retrospectively. The frequency of PP was evaluated. The presence of complete or partial PP in the atlas was examined on reformed sagittal cross-sectional images. Results: It was found that PP was detected in 250 patients (25%). When the prevalence of PP among gender was examined, it was found that 129 (24.2%) of 533 females and 121 (25.9%) of 467 males had PP. Complete PP was detected in 142 patients and partial PP was detected in a total of 151 patients. Discussion and Conclusion: In conclusion, PP is a common variation of the atlas. The increase in the frequency of complete PP and the decrease in the frequency of partial PP in older age groups suggested that there may be a correlation between age and PP formation.
Keywords: Anatomical Variation; Atlas Vertebrae; Cone-Beam Computed Tomography; Ponticulus Posticus